A multicenter study of self-limited epilepsy with centrotemporal spikes: Effectiveness of antiseizure medication with respect to spike-wave index - Dilber, Beril; Serdaroğlu, Esra; Kanmaz, Seda; Kılıç, Betül; İpek, Rojan; Kargın Menderes, Deniz; Yıldız, Nihal; Topçu, Yasemin; Arhan, Ebru Petek; Serdaroğlu, Ayşe; Okuyaz, Çetin; Aydın, Kürşad; et al. (Elsevier Inc., 2024)
Background: There is no certain validated electroencephalographic (EEG) parameters for outcome prediction in children with self-limited epilepsy with centrotemporal spikes. To assess the effectiveness of antiseizure medication (ASM) for seizure outcome with respect to the spike-wave index (SWI) on serial EEG recordings. Methods: In this multicenter study, the study cohort consisted of 604 children with self-limited epilepsy with centrotemporal spikes. A data set of epilepsy centers follow-up between 2010 and 2022. The cohort was divided into 4 groups as those receiving 3 different monotherapy (carbamazepine [CBZ]/valproic acid [VPA]/levetiracetam [LEV]) and dual therapy. SWI analysis was performed with the percent of spikes in the 2-minute epoch in the 5th 6th minutes of the nonrapid eye movement sleep EEG record. The study group were also categorized according to seizure burden with seizure frequency (I) >2 seizures and (II) >5 seizures. Seizure outcome was evaluated based on the reduction in seizure frequency over 6-month periods: (1) 50% reduction and (2) seizure-free (complete response). Results: ASM monotherapy was achieved in 74.5% children with VPA, CBZ, and LEV with similar rates of 85.8%, 85.7%, and 77.9%. Dual therapy was need in the 25.5% of children with SeLECT. More dual therapy was administered in children aged below 5 years with a rate of 46.2%. Earlier seizure-free achievement time was seen in children with LEV monotherapy with more complete-response rate (86.7%) compared the VPA and CBZ. Conclusions: We also determined that the children on dual therapy had more SWI clearance in the subsequent EEG recordings. The ROC curve analyses were performed to predict initial drug selection with using the SWI% might be used for the prediction of ASM type and drug selection in children.
Keywords: Antiseizure Medication; Pediatrics; Self Limited Epilepsy With Centrotemporal Spikes; Spike-Wave Index